Uma Avaliação do Programa de Apoio ao Arranjo Produtivo Local da Pedra Cariri – Ceará - Mendes Filho, Edilson (2009)
This study includes an ex post evaluation of the project Local Productive Arrangement Limestone Cariri. The evaluation of public projects, especially those of a socio-economic focused on disadvantaged communities, closed conceptual difficulties, technical and methodological rides, generators, often, conflicts and frustrations that discourage its systematic implementation. The main objective of this study is to evaluate the project developed by the Federal and State of Ceará governments, whose main goal was to develop a comprehensive action in the production chain of stone Cariri acting on factors that affect their technological development and competitiveness of micro and small enterprises that constitute it. For this literature review was performed on the basis of theoretical frameworks relating to Local Production and Public Policy reviews and field research with the target audience of the project to support the APL Stone Cariri, in order to assess the achievements of implementation of the project and seek to understand the process by which the project achieved or not their goals. In the field research were applied questionnaires to the chain, addressing the 16 targets in the project to support the APL, to investigate the perception of the actors concerning the results presented in the final project report. The results of field research indicate weaknesses in project implementation, particularly regarding the need for greater interaction with the audience, as well as the excessive number of targets in various aspects of the APL, which ultimately undermine the effectiveness of the project. Finally, we present the conclusions and suggestions to be followed in future projects, aiming to achieve the effectiveness of public policies managed.